2018
DOI: 10.1371/journal.pone.0197147
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anxiety and acute mountain sickness

Abstract: IntroductionWhilst the link between physical factors and risk of high altitude (HA)-related illness and acute mountain sickness (AMS) have been extensively explored, the influence of psychological factors has been less well examined. In this study we aimed to investigate the relationship between ‘anxiety and AMS risk during a progressive ascent to very HA.MethodsEighty health adults were assessed at baseline (848m) and over 9 consecutive altitudes during a progressive trek to 5140m. HA-related symptoms (Lake L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
5
37
1
Order By: Relevance
“…[ 15 , 217 ]. Such data are consistent with the information above about humans: indirect marker of susceptibility to AMS development may be increased anxiety at sea level [ 152 ]. On the contrary, in tolerant-to-hypoxia animals, excitability and anxiety are reduced, and moderate aggressiveness, more pronounced internal inhibition, low sensitivity to any provoking factors and a tendency to social domination are manifested, and they are more resistant to anesthesia.…”
Section: Physiological Biochemical and Molecular-biological Charsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 15 , 217 ]. Such data are consistent with the information above about humans: indirect marker of susceptibility to AMS development may be increased anxiety at sea level [ 152 ]. On the contrary, in tolerant-to-hypoxia animals, excitability and anxiety are reduced, and moderate aggressiveness, more pronounced internal inhibition, low sensitivity to any provoking factors and a tendency to social domination are manifested, and they are more resistant to anesthesia.…”
Section: Physiological Biochemical and Molecular-biological Charsupporting
confidence: 91%
“…An indirect marker of low tolerance to AMS development may be increased anxiety at sea level [ 152 ]. It was demonstrated that trait anxiety at low altitudes was detected as an independent predictor of future pronounced AMS development at a high altitude.…”
Section: Physiological Biochemical and Molecular-biological Charmentioning
confidence: 99%
“…Generally, the physical symptoms such as fatigue or headache may develop ascending rapidly to altitudes > 2500 m [15,16]. Moreover, the physical symptoms and impaired alveolar oxygen diffusion tend to be more severe over 4500 m [17].…”
Section: Discussionmentioning
confidence: 99%
“…Having an HCM relieved anxiety among the crew. This is notable because anxiety is associated with AMS according to the State-Trait-Anxiety-Inventory (STAI) 27) . Anxiety comprises current and sustained types, the latter of which is a predictor of severe AMS, and it is associated with AMS severity.…”
Section: Discussionmentioning
confidence: 99%